2010
DOI: 10.1016/j.cellsig.2010.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor-alpha mediated signaling in neuronal homeostasis and dysfunction

Abstract: Tumor necrosis factor-alpha (TNF-α) is a potent pro-inflammatory molecule, which upon engagement with its cognate receptors on target cells, triggers downstream signaling cascades that control a number of cellular processes related to cell viability, gene expression, ion homeostasis, and synaptic integrity. In the central nervous system (CNS), TNF-α is produced by brain-resident astrocytes, microglia, and neurons in response to numerous intrinsic and extrinsic stimuli. This review will summarize the key events… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
172
1
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(192 citation statements)
references
References 112 publications
5
172
1
5
Order By: Relevance
“…Studies have shown that S100B acts on receptors, such as the receptor for advanced glycation end products (RAGE), and its downstream pathways cause the production and secretion of inflammatory cytokines through the activation of NF-KB (21,22). In pathophysiological conditions, astrocytes and especially microglia release large amounts of TNF-α (23). An increased level of TNF-α has been reported in disorders such as Parkinson's disease, Alzheimer's disease, and multiple sclerosis (24,25).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that S100B acts on receptors, such as the receptor for advanced glycation end products (RAGE), and its downstream pathways cause the production and secretion of inflammatory cytokines through the activation of NF-KB (21,22). In pathophysiological conditions, astrocytes and especially microglia release large amounts of TNF-α (23). An increased level of TNF-α has been reported in disorders such as Parkinson's disease, Alzheimer's disease, and multiple sclerosis (24,25).…”
Section: Introductionmentioning
confidence: 99%
“…Because chronic morphine consumption has shown epigenetic effects and causes durable abnormal activities in the hippocampus (9,16,31,32), epigenetic modifications are inheritable from parents to their offspring (12), and TNF-α and S100B are present in the hippocampus and involved in anomalous hippocampal functions (18,23). In the current research study, we investigate the consequences of chronic consumption of morphine by both male and female parents before mating and gestation on the hippocampus TNF-α and S100B levels of the parents themselves and their offspring.…”
Section: Introductionmentioning
confidence: 99%
“…Recent data from transgenic murine AD models suggest that elevation of proinflammatory cytokines, including TNF, IL-1b, IL-6 and S100B, may precede the appearance of amyloid-b plaques [72]. Although the relative importance and inter-relationship of inflammatory pathways in AD is still being elaborated, a decade of accumulating scientific evidence suggests that excess TNF constitutes another target (in addition to amyloid and tau) that is a central mediator of AD pathogenesis (TaBle 2) [3-5,57, 70,[73][74][75][76][77][78]. This previously reviewed evidence includes:…”
Section: Scientific Rationale Role Of Tnf In Admentioning
confidence: 99%
“…9,10 Moreover, hCMEC/D3 cells were reported to mimic barrier characteristics of the BBB even in the absence of additional cell types, i.e., astrocytes or pericytes. 8 In this context, it was shown that tight junction (TJ) protein expression is specifically down-regulated in these cells in response to pro-inflammatory cytokines such as tumor necrosis factor (TNF), [10][11][12][13] suggesting that hCMEC/D3 cells represent a reliable tool to study inflammation-related modulation of the cerebral microvascular endothelial barrier function.…”
Section: Introductionmentioning
confidence: 99%